Design Improvement of Mold Bracket for Quarter Trim to Reduce Ejector Mark Defects - Agustin, Desy; Ma’ruf, Muhammad Irvan Tantyagus; Solih, Edwin Sahrial; Nurhadi, Fadhil Fadhlurrohman; Sumasto, Fredy (Universitas Muhammadiyah Yogyakarta, 2025)
This study focuses on improving the quarter trim bracket mold in the mold making division to mitigate the risk of ejector marks, which were identified through long-term analysis. The author redesigned the mold by considering the ejector layout, cooling layout, clamping force calculations, and number of pressure plates, to ensure the product is free from defects. The addition of an ejector pin in the rib area is proposed as a solution to minimize this problem. The quarter trim bracket mold is designed using two pressure plates measuring 30 x 60 mm and four measuring 30 x 80 mm, with a total pressure plate area reaching 13,200 mm². Based on calculations, this part requires a clamping force of 14.5 tons to be produced on a 30 ton capacity injection machine. This clamping force is important to keep the mold tightly closed during the production process, and is calculated based on the cavity pressure in the mold and the shot area. All mold designs are created following company standards to ensure accuracy of sizes and calculations. This research is expected to improve production quality and operational efficiency.